A wide-spectrum mid-infrared electro-optic intensity modulator employing a two-point coupled lithium niobate racetrack resonator - Hwang, Hyeon; Ko, Kiyoung; Nurrahman, Mohamad Reza; Moon, Kiwon; Ju, Jung Jin; Han, Sang-Wook; Jung, Hojoong; Seo, Min-Kyo; Lee, Hansuek (AIP Publishing LLC | American Institute of Physics, 2025)
Optical intensity modulators (OIMs) are essential for mid-infrared (mid-IR) photonics, enabling applications such as bond-selective molecular sensing, and free-space communications via atmospheric windows. Integrated photonics offers a compact and cost-effective solution, yet on-chip mid-IR OIMs significantly underperform compared to their near-IR counterparts. Furthermore, despite the potential benefits for system reconfiguration in accessing various communication frequencies and molecular absorption bands, developing a single OIM capable of operating across a broad spectral range remains a challenge. In this study, we introduce an on-chip OIM that operates over a wide wavelength range in the mid-IR, implemented using a racetrack resonator structure in thin film lithium niobate (TFLN). The modulator employs a two-point coupling scheme, allowing active control of the coupling strength to maintain critical coupling and thereby ensuring high modulation extinction across a wide spectral region. This approach not only achieves high modulation performance but also relaxes the design constraints and fabrication precision typically associated with resonator-based modulators, as confirmed through an analytic model. Implemented in TFLN having a wide transmission spectrum and strong electro-optic coefficient, the OIM demonstrates a modulation extinction ratio exceeding 20 dB with an electro-optic efficiency of 7.7 V cm over the wavelength range of 3.3-3.8 mu m, which falls within the first atmospheric transmission widow in the mid-IR. This approach can be adapted to other spectral regions, providing a versatile solution for diverse photonic applications. (c) 2025 Author(s). All article content, except where otherwise noted, is licensed under a Creative Commons Attribution-NonCommercial-NoDerivs 4.0 International (CC BY-NC) license (https://creativecommons.org/licenses/by-nc/4.0/).